Uji Hedonik Kue Apem dengan Penambahan Bubuk Kayu Manis dan Tepung Labu Kuning - I Made Purwa Dana Dana (JURNAL GASTRONOMI INDONESIA, 2020)
This study aims to describe the processing process of apem cake with the addition of cinnamon powder and pumpkin flour in its manufacture using an experimental method as well as to determine the level of consumer preference for the modified apem cakes. The apem cake is processed with a recipe modified from the standard recipe by adding cinnamon powder. The results were given to 100 panelists using the five senses: the taste, the smell/aroma, the color and the texture. This experiment was carried out in the kitchen of the Bali Tourism Polytechnic. The data collection technique used were experiments, documentation, and hedonic testing. The analysis technique used was descriptive quantitative using Likert scale. The results of the study showed that the favorite results of the apem cake with the addition of cinnamon powder and pumpkin flour with assessment criteria in terms of taste, aroma, texture and color with a total average value of 82,4% and the interpretation criteria to like it very much.